PENGARUH PENGALAMAN, ORIENTASI ETIKA, DAN KOMITMEN TERHADAP SENSITIVITAS ETIKA AUDITOR (Studi Empiris Pada Kantor Akuntan Publik Kordinator Wilayah Sumbateng dan Sumbasel) - R. Adib Al Khalish; Yuneita Anisma; M Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study purpose to obtain empirical evidence regarding the influence of Experience, Orientation Ethics, and Commitment to the Sensitivity of Auditor Ethics. This research is included in quantitative research. Population in this research is Auditor performing examination function at Public Accountant Office of Area Coordinator in Sumbateng and Sumbasel. The sample of this research is auditor who works in 22 Public Accounting Firm (KAP) that exist in representatives of region Sumbateng and Sumbasel that is Pekanbaru, Jambi, Palembang, and Bandar Lampung. The sampling technique used is purposive sampling technique with 65 respondents. Methods of data collection using questionnaires distributed to respondents. Scale of measurement data with Likert scale. Data were analyzed by using multiple regression analysis with SPSS version 25.0 program. The result of the research shows that (1) there are positive and significant influence of Experience to Ethical Sensitivity, (2) there is positive and significant influence of Ethical Orientation to Ethical Sensitivity, (3) there is positive and significant influence Commitment to Ethical Sensitivity.Keyword : Experience, Orientation Ethics, Commitment, Ethical Sensitivity.